Pengaruh Pemangkasan Terhadap Pertumbuhan dan Hasil Bunga Kenikir Sulfur (Cosmos sulphureus) - Artamefia, Yosi; Kalsum, Ummu; Perkasa, Achmad Yozar (Politeknik Pertanian Bogor, 2025)
The sulfur cosmos (Cosmos sulphureus) is a horticultural plant with high potential for cultivation as an ornamental, food source, and medicine. However, cultivation methods remain limited and not intensive. Pruning is a cultivation technique that can increase crop yields. This study analyzed the response of sulfur cosmos plants to pruning on growth and flower yield, and identified the most effective pruning treatment for increasing flower yield of sulfur cosmos. The research was conducted at the Greenhouse Beta UG Technopark from January to May 2025. The research used a non-factorial randomized complete block design (RCBD) with five treatments, control (no pruning), pruning at 5 weeks after planting (WAP) to a height of 30 cm above ground level, pruning at 6 WAP to a height of 30 cm, pruning at 5 WAP to a height of 35 cm, and pruning at 6 WAP to a height of 35 cm. Each treatment had five replicates with four plants each, totaling 100 plants. The results showed that pruning significantly affected plant height, number of lateral shoots, number of primary and secondary branches, number of productive branches, leaf area, total fresh and dry flower weight per plant, harvest frequency, and total number of flowers. Pruning at 5 WAP to a height of 30 cm above ground level was the most effective treatment to increase flower yield in terms of total fresh and total dry flower weight per plant, harvest frequency, and total number of flowers.